2018
DOI: 10.1103/physrevb.97.245416
|View full text |Cite
|
Sign up to set email alerts
|

Resonant electron-lattice cooling in graphene

Abstract: Controlling energy flows in solids through switchable electron-lattice cooling can grant access to a range of interesting and potentially useful energy transport phenomena. Here we discuss a tunable electron-lattice cooling mechanism arising in graphene due to phonon emission mediated by resonant scattering on defects in a crystal lattice, which displays an interesting analogy to the Purcell effect in optics. In that, the electron-phonon cooling rate is enhanced due to hot carrier trapping at resonant defects.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 29 publications
2
33
1
Order By: Relevance
“…This high-resolution thermography was employed to study dissipation in graphene [15], where dissipation ring-shaped spots were observed in the bulk and on the edge of the samples, and associated with individual atomic defects. This interpretation was supported by the theory of "resonant supercollisions" [16,17]. Although Ref.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…This high-resolution thermography was employed to study dissipation in graphene [15], where dissipation ring-shaped spots were observed in the bulk and on the edge of the samples, and associated with individual atomic defects. This interpretation was supported by the theory of "resonant supercollisions" [16,17]. Although Ref.…”
Section: Introductionmentioning
confidence: 85%
“…It possesses the key properties of the electron-phonon collision integrals: it vanishes in equilibrium, conserves the total number of electrons, and does not transfer energy to < 0. The Fokker-Planck form of the collision integral (3) can be microscopically derived for the quasi-elastic scattering by acoustic phonons [20] for T T BG , where T BG is the Bloch-Grüneisen temperature which determines the maximum energy transferred from electron to acoustic phonons in a collision process (in the absence of impurity-assisted "supercollisions" [16,17,21]).…”
Section: Modelmentioning
confidence: 99%
“…With the Hamiltonian introduced above, we can calculate the energy dissipation induced by the presence of a resonant impurity. In contrast to the 2D case, where energy dissipation originates from the particle scattering in all directions [18,19], only forward scattering at the impurity is operative in the chiral QH edge. This only introduces a phase factor in the wave function.…”
Section: Resonant Scattering and Thermal Ringsmentioning
confidence: 89%
“…The resonant character of dissipation in Eq. (15) bears similarity to resonant supercollisions in the 2D graphene bulk [18,19]. However, the chiral 1D case is distinct in several respects.…”
Section: Dissipation Induced By Resonant Impuritiesmentioning
confidence: 92%
See 1 more Smart Citation